Facilities management of bus terminal (case study: Larkin Bus Terminal, Johor, Melaka Sentral, Melaka and Terminal One, Seremban / Mohammad Ashraf Abdul Rahman - Abdul Rahman, Mohammad Ashraf (2006)
Terminal plays an important role in the public transportation in Malaysia. It acts as a place of arrival and departure and as a transit exchange for buses before they go on the next destination. Bus terminal is well facilitating for the comfort of the passengers. As a waiting place for the passengers, bus terminal should be well equipped. These terminals not only service the express buses but also the town buses and taxis. Tickets counter are also available here. There is some terminal that adjourned to other building for another purpose. The sites for bus terminal are commonly located in the city centre, outside the city centre or at the fringe of city centre. Wherever the site may be located, the terminal should serve or provide its basic function, which rendered safety and convenient to the users while waiting, alighting or boarding the bus. A well planned and managed bus terminal will act as catalyzed to the development of the surrounding areas. Inadequate facilities such as toilets, telephone, surau and others physical facilities will give the bad image to the terminal. Sometimes the facilities is not well maintained which lead to dissatisfaction among the users. These facilities should be addressed and planned earlier during design stage and construction in order to accommodate the facilities and flexibility for all users. Therefore providing these facilities will be more efficient and effective.